Peramalan Penjualan Pipa di PT X - Elviani, Cicely; Halim, Siana (Jurnal Titra, 2014)
In this thesis we modeled the sales pipeline using auto regressive moving average, ARIMA(p,d,q) under R-Software. Those selected models are used to forecast the standard water pipe and black, standard water pipe and medium standard black pipe, SCH 40 standard water pipe and black, BDA standard water pipe, standard water pipe, medium B, coil, and furniture pipe future demands.